UPAYA PENURUNAN NYERI DADA PADA PASIEN GAGAL JANTUNG DI RSUD dr. SOEHADI PRIJONEGORO - marenda, Ardiyan Dika, Okti Sri Purwanti, S.Kep, Ns (2016)
Background: The prevalence of heart failure incident in Indonesia has increased sharply each year. Elderly or aging is the major risk factor of heart failure. Moreover, heart failure can causes symptoms such as chest pain. Chest pain arises due to the lack of oxygen supply in the myocardium, and this will impact to the damage of the heart cells. If this pain is not treated well, the severity of the pain will increase. And this will lead to the neurological shock in the person with heart failure. Objective: To Describe the efforts in reducing chest pain in the patient with heart failure. Method: Method applied a descriptive method with a case study approach conducted in the inpatient installation room of Sakura at dr. Soehadi Prijonegoro from the 29th to 31st of March 2016. The data was collected through observation, physical examination, medical records, interviews, documentary studies of related journals and books. Results: The patient indicated decrease of the chest pain after the treatment. As for the effect of the relaxation treatment such as deep breath and warm compresses to reduce the chest pain. Conclusion: The relaxation treatment such as deep breath and warm compresses has effectively decrease the chest pain. Suggestion: The relaxation treatment such as deep breath and warm compresses can be used as an option in the independent nursing treatment to deal with pain.